Clinical Characteristics of and Services Provided for Patients with Lymphedema Referred to a Physiotherapy Program During the Years 2009 Through 2019 - DUMAN ÖZKAN, TUĞÇE (MARY ANN LIEBERT, INC, 2021)
Background: Lymphedema is a chronic and progressive disease whose diagnosis involves determination of clinical and demographic characteristics. The aim of this retrospective study was to analyze the clinical characteristics of patients with lymphedema and their various diagnoses. We studied patients who were referred for physiotherapy services at any point during the years 2009 through 2019. Methods: Retrospective data were collected from the files of 430 lymphedema patients. The type, cause, localization, stage, and severity of lymphedema and physiotherapy needs were analyzed and reported. Results: Primary and secondary lymphedema were observed in 18 (4.2%) and 412 (95.8%) patients, respectively. The patients' mean body mass index score was 30.66 kg/m(2). The data indicated that the most common cause of secondary lymphedema was breast cancer and its treatments (n = 196, 47.6%). Other causes were chronic venous insufficiency (CVI) (n = 140, 34%), lipolymphedema (n = 11, 2.7%), and other types of cancers (n = 65, 15.7%). According to the affected body regions, 416 patients had unilateral/bilateral upper and lower extremity lymphedema and 14 had head and neck lymphedema. The patients were followed with a home-based physiotherapy program (n = 353, 82.1%) or they underwent treatments through an outpatient program (n = 77, 17.9%). Conclusions: Most patients admitted to the clinic had a diagnosis of breast cancer and CVI. The severity and stages of lymphedema were variable. The data indicated that most patients were followed through a home-based physiotherapy program. These results may set a frame for understanding the treatment and care needs of patients with lymphedema.
Keywords: cancer; venous insufficiency; complex decongestive physiotherapy; lymphedema treatment; COMPLEX DECONGESTIVE PHYSIOTHERAPY; QUALITY-OF-LIFE; BREAST-CANCER; PSYCHOSOCIAL IMPACT; ARM LYMPHEDEMA; THERAPY; OBESITY; HEAD; DIAGNOSIS; EDEMA